Hybrid and Performative Spaces: Towards a New Analytical Lens - Kassem, Ayman (UI Scholars Hub, 2022)
The exhibition space is a territory where architects and designers have experimented with hybrid and performative spatial qualities. However, such spatial mechanisms have expanded into other spatial practices. As we live in a constantly changing world, these practices allow spatial systems that adjust to continual changes in modes of living. Newer approaches to spatial transformation try to respond to the need for transience and flexibility. Hybrid and performative interventions are elaborated to transform existing spaces with strategic non-architectural rearrangements. As a result, our inhabited spaces, such as exhibitions, are becoming hybrid and performative. However, hybrid and performative may be perceived as tools, or as resulting qualities. The literature review analysis shows many intersections between hybrid and performative. Both terms indicate a flexible built environment that is designed and organised to be multifunctional. Hybrid mostly refers to the various modes of accessing, using and being present in the space, while performative refers to the concept of flexible mechanisms, the openness towards changes and the unpredictable characterisation of a space. Performative is also linked to the ability of the space to multitask and perform different roles, including communicative tasks. This study investigates the repertoire of hybrid and performative through an analysis of a literature review conducted through the lens of exhibition design. We seek to explore and promote applications in spatial interventions and the potential to define a set of analytical tools. Seeing the emergence of a constantly changing world, spatial disciplines are trying to respond with flexible mechanisms. Therefore, newer critical lenses, scholarships, and analytical tools must be investigated, explored, and proposed to cope with such continuous shifts.